480 Cardiovascular and metabolic risk in patients with suspected comorbid insomnia and obstructive sleep apnea (COMISA). (3rd May 2021) - e Cruz, Miguel Meira; Seixas, Luana; Santos, Augusto; Garrido, João; Lopes, Yuri; Palombini, Luciana; Gozal, David; Galtieri, Ranuzia; Salles, Cristina
Abstract: Introduction: Only few studies looked for a possible association of cardiovascular disorders (CVD), in comorbid insomnia with obstructive sleep apnea (COMISA) even though this is a relevant topic in order to prevent one of the major causes of morbimortality. The present study aimed to investigate the association of insomnia symptoms in patients at risk for obstructive sleep apnea in terms of prevalence and clinical interactions and to evaluate the risk of CVD in patients with a risk for COMISA. Methods: This is a cross-sectional study. All medical records with data such as age, sex, height, weight and BMI, time to sleep, time to wake up, total sleep time, the Epworth Sleepiness Scale (ESS), STOP-BANG Questionnaires were studied. Insomnia and comorbidities were also investigated, and the patientsanswered yes or no to systemic arterial hypertension, diabetes, CVD. Results: 685 patients were enrolled on the present study. We observed that the mild, moderate, and high risk for COMISA presented progressively increasing levels for the frequency of hypertension, diabetes, and CVD. A binary logistic regression was performed to assess whether risk for COMISA could be a predictor for CVD, and it was found that the model containing risk for COMISA was statistically significant: [x2(1)=5.273;p<0.021, R2 Negelkerke=0.014]. Risk for COMISA presented itself as a significant predictor for CVD (OR=1.672; 95% CI=1.079–2.592). Conclusion: There was an increased frequency of associated comorbidities such as CVD, systemic arterial hypertension, and diabetes, according to the mild, moderate, or high risk. These findings highlight the need for a cardiometabolic evaluation in patients with this comorbid condition which may impact prognosis and therapeutic success. Support (if any):